2001
DOI: 10.1007/s003830100592
|View full text |Cite
|
Sign up to set email alerts
|

The effect of phospholipids and fatty acids on tight-junction permeability and bacterial translocation

Abstract: The activity of phospholipase A2 (PLA2) is elevated in the intestinal epithelia of patients with inflammatory bowel disease (IBD). We recently reported that PLA2 mediates hydrolysis of phosphatidylcholine (PC) to lysophosphatidylcholine (L-PC) when both are applied to the apical surface of cultured EC monolayers, resulting in increased bacterial translocation (BT) and decreased transepithelial electrical resistance (TEER). Free fatty acids (FFA) are the other products of this reaction, however, their effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Other possible changes in the cellular architecture and composition of the digestive tract might favour parasite entrance and proliferation in the intestinal epithelium, through changes at the host-parasite interface (Yoshino et al, 2001), alterations of the gut barrier or the mucosal immunity (Kasper and Buzoni-Gatel, 2001), or alterations of the biochemical makeup of the cell membrane lipid rafts/caveolae microdomains (Chapkin et al, 2008). In fact, the effect of PLs, FAs and soybean meal on tight-junction permeability and therefore in bacterial translocation (Sawai et al, 2001), on fish intestinal mucus and bacterial adhesion (BakkeMcKellep et al, 2007;Schroers et al, 2008) have been reported. Thus, further studies are needed to determine the effect of vegetable diets in the distribution and composition of enzymes, other molecules of interest and leucocyte populations in the intestinal tract.…”
Section: Discussionmentioning
confidence: 98%
“…Other possible changes in the cellular architecture and composition of the digestive tract might favour parasite entrance and proliferation in the intestinal epithelium, through changes at the host-parasite interface (Yoshino et al, 2001), alterations of the gut barrier or the mucosal immunity (Kasper and Buzoni-Gatel, 2001), or alterations of the biochemical makeup of the cell membrane lipid rafts/caveolae microdomains (Chapkin et al, 2008). In fact, the effect of PLs, FAs and soybean meal on tight-junction permeability and therefore in bacterial translocation (Sawai et al, 2001), on fish intestinal mucus and bacterial adhesion (BakkeMcKellep et al, 2007;Schroers et al, 2008) have been reported. Thus, further studies are needed to determine the effect of vegetable diets in the distribution and composition of enzymes, other molecules of interest and leucocyte populations in the intestinal tract.…”
Section: Discussionmentioning
confidence: 98%
“…Fatty acids are the major constituents of the phospholipid bilayer of the epithelial cell membrane and have been suggested to play a role in modulating the permeability of the epithelial cells [29]. Yamagata and his colleagues [42] recently reported that EPA and glinolenic acid (GLA), by modulating protein kinase C and tyrosine kinase activity, increased the expression of occludin mRNA in porcine brain capillary endothelial cells, leading to an increased TEER in their barrier model.…”
Section: Discussionmentioning
confidence: 99%
“…Another study using cultured enterocytes showed that PLA 2 (which is increased in IBD patients), converts PC to LPC, leading to increased tight junction permeability and bacterial translocation. 51 Several animal studies have shown protection from experimental colitis when given exogenous sources of PC in the diet. 52,53 Another key component of mucus is mucin (a glycoprotein) that has also been found to be selectively abnormal in UC patients, but not those with colitis from CD, infection, or ischemia.…”
Section: Lipid Metabolism In Ibdmentioning
confidence: 99%